Inflation, economic growth and education expenditure - Sequeira, Tiago Neves (2021)
Recent evidence shows that different inflation rates have effects on long-run economic growth. We follow the increasing interest in the issue offering a new explanation for the influence of monetary policy on economic growth: cash re¬quirements for household expenditures in education. We devise an endogenous growth model with cash-in-advance (CIA) constraints in several sectors (education, horizontal R&D, vertical R&D, and manufacturing and consumption) and study its steady-state and transitional dynamics. In particular, the CIA con¬straint in education expenditures of households is essential to obtain a negative relationship between inflation and economic growth in the long-run. Quan¬titatively, this monetary endogenous growth model replicates both the small influence of monetary policy on growth, while highlighting the effects it can have on welfare and the allocation of resources in different sectors of the economy